INTERNAL COMMUNICATION SYSTEMS AND INVESTOR SERVICE PERFORMANCE: EVIDENCE FROM AN INDUSTRIAL ESTATE COMPANY IN INDONESIA - Lestari, Budi; Prasetyo, Kurniawan; Majeed, Ali Nazar (Universitas Mercu Buana, 2025)
This study examines the effectiveness of internal communication systems in enhancing investor service performance, with empirical evidence from an industrial estate company in Indonesia. In the contemporary organizational context, effective internal communication is a strategic resource that supports coordination, accuracy, and service responsiveness, particularly in investor-oriented services. Grounded in Organizational Communication Theory, this research adopts Hardjana’s communication effectiveness framework, which emphasizes receiver, content, media, format, source credibility, and timing as key dimensions. The study aims to assess the effectiveness of the Dynamic Archival Information System (SIKD) as an internal communication medium in supporting investor services at PT Jakarta Industrial Estate Pulogadung (PT JIEP). This research employs a quantitative descriptive approach using a survey method. Data were collected through structured questionnaires distributed to 77 employees directly involved in administrative and investor service activities. The data were analyzed using descriptive statistics and the Likert Summating Rating (LSR) technique to measure the effectiveness of the internal communication system. The results indicate that SIKD is highly effective as an internal communication medium, with the overall score falling into the “very effective” category. All six dimensions of communication effectiveness demonstrate strong performance, with timeliness and source credibility emerging as the most dominant factors. These findings are consistent with organizational communication theory, which posits that effective internal communication enhances coordination and service quality. The study confirms that a well-managed internal communication system significantly contributes to improved investor service performance. In conclusion, this research highlights the strategic role of digital internal communication systems in supporting investor services. Effective internal communication not only strengthens internal coordination but also enhances organizational credibility and service excellence in investor relations